The Psychological impact of Harry Potter on the Youth (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The book and film series Harry Potter and its widespread appeal among readers of all ages is the subject of this study. There is a lot of mysticism and supernaturalism in this fantasy literature. In addition to analysing the psychological impact of reading or seeing this book, it explains the gender ratio of its audience. Compared to other fantasy films and literature of the same era, this article examines why Harry Potter became an international phenomenon. Additionally, it delves into the impact of Harry Potter on the modern era. In light of Harry Potter, it analyses the lessons that individuals took away from it. A survey format was used for the investigation. Questions regarding the influence of Harry Potter on viewers' or readers' mental health, as well as their favourite lines and language from the series, were included of the survey. Viewers' or readers' belief in the occult or supernatural is also examined in the study. Furthermore, it investigates the age bracket in which it is most widely read and seen, as well as the medium through which it has achieved this level of success. You may also get the ratio of views to reads in it. It delves deeper into the question of whether individuals were influenced to suggest it to others.